Expression of heterosis, heterobeltiosis, and gene action in quantitative characters on soybean (Glycine max) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Krisnawati A, Adie MM. 2022. Expression of heterosis, heterobeltiosis, and gene action in quantitative characters on soybean (Glycine max). Biodiversitas 23: 1745-1751. Most soybean (Glycine max (L.) Merrill) varieties have been created by crossing two or more parental genotypes. The study aimed to quantify the value of heterosis, heterobeltiosis, the degree of dominance as well as the gene action of the agronomic characters of F1 plants derived from the four soybean cross combinations. All the parents and crosses were evaluated in the screen house of the Indonesian Legume and Tuber Crops Research Institute (Malang, East Java, Indonesia) during 2021. The estimation for mid-parent heterosis (hMP), high-parent heterosis or heterobeltiosis (hHP), degree of dominance, and gene action was done for sevenquantitative characters (plant height, number of branches, number of nodes, number of filled pods, number of empty pods, weight of 10 seeds, and seed yield). The performance of the quantitative characters differs among cross combinations. The estimated value of heterosis mid-parent (hMP) for F1 crosses from four parental combinations ranged from -61.20 to 27.57, heterobeltiosis (hHP) ranged from -71.17 to 9.84, and the degree of dominance ranged from -6.45 to 19.40. The crosses of Derap 1 × Gepak Kuning and Dering 1 × Gepak Kuning showed a positive hMP and hHP for seed yield character. Thus, these hybrids could be used to develop high-yielding varieties with desirable traits in soybean. Seed yield character in the cross of Derap 1 × Gepak Kuning exhibited the overdominance type of gene action, meanwhile, the Dering 1 × Gepak Kuning was incomplete dominance.